The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/elan.201900072
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric Electronic Tongue Based on Carbon Paste Electrodes Modified with Biochar for Phenolic Compounds Stripping Detection

Abstract: Biochar is a charcoal produced from the biomass pyrolysis process that presents a highly porous and functionalized surface. In the present work an array of carbon paste electrodes (CPE) made of different forms of carbon (graphite, carbon nanotubes and activated biochar) was evaluated in the development of an electronic tongue for discrimination and stripping voltammetric determination of catechol (CAT), 4‐ethylcatechol (4‐EC) and 4‐ethylguaiacol (4‐EG) phenolic compounds. Morphological characterization of carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 62 publications
0
6
0
1
Order By: Relevance
“…Nevertheless, the accuracy of this prediction was slightly lower than that observed using random forest (R 2 = 0.996, MSE = 0.0012). Previous studies [28,29] showed that the use of FNN as a data regression method in the development of sensors based on electrochemical measurements provided prediction results with high precision. However, to the best of the authors' knowledge, this is the first study to predict the concentration of a compound using key features from multimodal data (ECL imaging and amperograms) into a single FNN.…”
Section: Feedforward Neural Network (Fnn) Prediction Resultsmentioning
confidence: 99%
“…Nevertheless, the accuracy of this prediction was slightly lower than that observed using random forest (R 2 = 0.996, MSE = 0.0012). Previous studies [28,29] showed that the use of FNN as a data regression method in the development of sensors based on electrochemical measurements provided prediction results with high precision. However, to the best of the authors' knowledge, this is the first study to predict the concentration of a compound using key features from multimodal data (ECL imaging and amperograms) into a single FNN.…”
Section: Feedforward Neural Network (Fnn) Prediction Resultsmentioning
confidence: 99%
“…For both electrochemical techniques a typical three electrode circuit was used. In the used assembly it can be found: the working electrode based on a graphite epoxy composite (electrode already optimized in our laboratory [ 39 , 40 , 41 ]), an Ag/AgCl (0.1 mol·L −1 KCl) electrode as a reference and a Pt electrode as a counter. All measurements were carried out at room temperature without stirring using as an electrolyte solution phosphate buffer 50 mmol·L −1 + KCl 100 mmol·L −1 at pH 7.4.…”
Section: Methodsmentioning
confidence: 99%
“…The reason is based not only on the procedure of the preparation, but also on the fact that the demand of the mixed modifier in the preparation of carbon-paste electrodes is easier and lower than that of screen-printed electrodes. Kalinke et al, have carried out several works regarding the preparation of carbon-paste electrodes by mixing biochar as the modifier [ 33 , 34 ]. For example, their recent work involved the preparation of biochar by pyrolysis of a castor cake waste biomass at 400 °C [ 34 ].…”
Section: The Role Of Biochar In the Fabrication Of Electrochemical Se...mentioning
confidence: 99%